Kegiatan preservasi di Pustakalana Children’s Library - Osama Muhammad Fikri; Maula Siti Sarah (Jurnal Informatio, 2022)
With the background of the importance of preservation activities, a library needs to be the main headline in library activities. Moreover, as the scope of the library's duties, preservation is a mandatory activity that is owned to extend the life of a collection. The author conducted research on the children's library, Pustakalana Children's Library to find out the preservation activities carried out at Pustakalana. This study uses a qualitative descriptive research method with a case study approach in which non-quantitative data will be interpreted descriptively. The selection of sources as primary data acquisition, using purposive sampling method. The resource person chosen by the author is the head of the Pustakalana librarian, which is none other than the proximity of the librarian in preservation activities. Furthermore, observations were made for the acquisition of secondary data and a literature review to obtain tertiary data to support primary and secondary data. Data analysis used three stages, namely, data reduction, data presentation and drawing conclusions and verification. The results show that preservation activities in Pustakalana include active conservation activities that are directly related to library collections such as wrapping books, passive conservation which is carried out by conditioning the environment around the collection starting from the optimal room temperature in Pustakalana at 20˚C - 23˚C. , humidity levels, air circulation to sunlight, and preventive conservation related to the formulation of policies and operational standards regarding preservation and conservation activities themselves. Furthermore, it is important to recognize the factors that cause damage to a collection in Pustakalana divided into two, namely, internal factors include collection characteristics, and external factors include environment, humans, natural disasters and biota. It was concluded that Pustakalana was very aware of the importance of preservation activities in the library. Pustakalana has done both passively, actively and preventively to extend the life of its library collections.